Towards Optimization of Patients’ Turnaround Time using Bluetooth Low Energy Based Solutions - Muthu Arumugam, Ganes Raj; Muthaiyah, Saravanan; Zaw, Thein Oak Kyaw (Journal of Telecommunications and the Digital Economy, 2022)
Smart Healthcare can use the Internet of Things (IoT) to broaden the reach of digital healthcare by collecting patient data remotely using sensors. This can reduce Patient Turnaround Time (PTAT) and enable high-quality care to be provided. PTAT is the length of time from when a patient arrives at the hospital until they are allowed to return home. Malaysia's Ministry of Health claimed in 2016 that healthcare at government hospitals continues to encounter issues in providing high-quality care to patients, particularly in terms of the PTAT of patients who receive treatment versus those who are sent home without treatment. In this paper, we propose a Bluetooth Low Energy-based solution that optimizes PTAT using low calibrated transmission power, allowing hospitals to enable Real-time Patient Localization and Patient Movement Monitoring. The RSSI value is used to calculate the distance between a wearable device and the Access Points (AP) situated throughout the facility. When a patient passes an AP, data such as the wearable device name and RSSI value are taken and saved in a database, to determine the patient's location. A proof of concept was conducted using three AP points and 8 wearable devices to gauge distance measurement.